Lesão perfurocontundente causada por projétil balístico em cão - Almeida, Gabrielle de [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This paper describes the activities developed at the Department of Pathology, Reproduction and One Health at UNESP FCAV - Campus de Jaboticabal, from June to September 2021, such as the collection of material through biopsies or necropsies for histological analysis, all its processing, reading and diagnosis. In addition, it addresses the importance of forensic veterinary medicine and its rise in today's society, emphasizing how the development of the specialty becomes essential. The main objective of this review is to promote a theoretical basis on forensic ballistics, as well as its collaboration in veterinary necropsy, in order to carry out the process as efficiently as possible. It is proposed, therefore, to present the techniques that should be used during this procedure and which aspects require more careful study.

O presente trabalho descreve as atividades desenvolvidas no Departamento de Patologia, Reproduçao e Saúde Única da UNESP FCAV - Campus de Jaboticabal, de junho a setembro de 2021, como a coleta de material através de biópsias ou necrópsias para análise histológica, todo seu processamento, leitura e diagnóstico. Além disso, aborda a importância da medicina veterinária legal e sua ascensão na atual sociedade, ressaltando como o desenvolvimento da especialidade se torna imprescindível. O objetivo central desta revisão é promover uma base teórica sobre balística forense, bem como sua colaboração na necropsia veterinária, a fim da realização do processo com maior eficiência possível. Propõe-se, assim, apresentar as técnicas que devem ser utilizadas durante a realização deste procedimento e quais aspectos demandam estudo mais criterioso.
Blunt puncture injury caused by a ballistic projectile in a dog
Keywords: Histologia veterinária; Balística forense; Biobalística; Necropsia veterinária; Medicina veterinária legal